Revisit of metallothermic reduction for macroporous Si: compromise between capacity and volume expansion for practical Li-ion battery. (March 2015) - Choi, Sinho; Bok, Taesoo; Ryu, Jaegeon; Lee, Jung-In; Cho, Jaephil; Park, Soojin
Abstract: We revisit the metallothermic reduction process to synthesize shape-preserving macro-/nanoporous Si particles via aluminothermic and subsequent magnesiotheric reaction of porous silica particles. This process enables us to control the specific capacity and volume expansion of shape-preserving porous Si-based anodes. Two step metallothermic reactions have several advantages including a successful synthesis of shape-preserving Si particles, tunable specific capacity of as-synthesized Si anode, accommodation of a large volume change of Si by porous nature and alumina layers, and a scalable synthesis (hundreds of gram per batch). An optimized macroporous Si/Al2 O3 composite anode exhibits a reversible capacity of ~1500 mAh g −1 after 100 cycles at C/5 and a volume expansion of ~34% even after 100 cycles. Graphical abstract: Shape-reserving macroporous Si/Al2 O3 composite can be synthesized by two-step metallothermic reaction. This process enables us to control a reversible capacity of a volume expansion of Si-base anode materials for practical lithium-ion battery applications. Optimized Si-based composite electrodes show a reversible capacity of 1500 mAh g −1 at C/5 with minimized volume expansion (<35%) after 100 cycles. Highlights: We revisited the metallothermic reduction to synthesize shape-preserving macro/nanoporous Si particles. Two-step reduction reaction enabled us to control the specific capacity and volume expansion of porous Si-based anodes. Macro/nanoporous Si anode showed a reversible capacity of 1500 mAh g −1 after 100 cycles and a volume expansion of 34% even after 100 cycles.